Evaluation of Urinary hsa-miR-21-5p Expression as a Non-Invasive Biomarker for Prostate Cancer - Resa Paksi Mandariska; Adzka Fahma Rodliya (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Prostate cancer is one of the most common malignancies among men worldwide. Prostate-specific antigen (PSA) testing and prostate biopsy are commonly used for diagnosis. However, these methods may be invasive and can lead to delayed detection in some cases. This study aimed to evaluate the expression of hsa-miR-21-5p in urine samples from prostate cancer patients compared with healthy individuals to assess its potential as a non-invasive biomarker.Methods: This observational study used a cross-sectional design and was conducted in Yogyakarta, Indonesia, between October and December 2018. Expression profiling of hsa-miR-21-5p was performed using quantitative real-time polymerase chain reaction (qRT-PCR) in urine samples obtained from 12 prostate cancer patients and 8 healthy controls. Relative expression levels were analyzed using GenEx software and calculated using the Livak (2^−ΔΔCt) method.Results: The age of prostate cancer patients ranged from 60 to 83 years, whereas the healthy control group had a mean age of 53.88 ±2.59 years (range 50–58 years). A slight decrease in hsa-miR-21-5p expression was observed in urine samples from prostate cancer patients compared with healthy controls (fold change=0.7; p>0.05).Conclusion: Expression of hsa-miR-21-5p shows a tendency toward downregulation in urine samples of prostate cancer patients, however, no statistically significant difference is identified. Further studies with larger sample sizes are required to clarify its potential role as a non-invasive biomarker for prostate cancer detection.